2011
DOI: 10.1159/000334416
|View full text |Cite
|
Sign up to set email alerts
|

Finasteride Adherence-Associated Factors in Chinese Benign Prostatic Hyperplasia Patients

Abstract: Objectives: Medication noncompliance is a recognized problem worldwide. This study evaluated the factors associated with compliance, discontinuation and switching of finasteride among Chinese benign prostatic hyperplasia patients. Materials and Methods: A retrospective cohort study was conducted with 682 outpatients newly diagnosed with benign prostatic hyperplasia and prescribed with finasteride from January 2008 to December 2009, taken from a database. We evaluated their compliance by medication possession r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…With the aid of carers, patients miss their medications less frequently, receive better social or family support and are better informed about their medications [25][26][27][28]. Thus, the findings of our study support better adherence seen in older BPH patients described in previous studies [17,18].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…With the aid of carers, patients miss their medications less frequently, receive better social or family support and are better informed about their medications [25][26][27][28]. Thus, the findings of our study support better adherence seen in older BPH patients described in previous studies [17,18].…”
Section: Discussionsupporting
confidence: 80%
“…This study found that patients younger than 65 years of age were more likely to have issues regarding their current medications than those who were older than 65. This information helps explain the reasons for poor adherence in younger patients with BPH as described in previous studies [17,18]. Older adults, female gender, and consumers' belief that therapy will help are additional predictors of adherence [20].…”
Section: Discussionmentioning
confidence: 76%
“…Combination therapies seem to result in better compliance compared with monotherapies [Lin et al 2012;Nichol et al 2009]. Less-frequent dosage enhances adherence and technical adherence interventions are usually directed at simplifying the medication regimen [Van Dulmen et al 2007].…”
Section: Cost-effectiveness Of the Fdc And Adherencementioning
confidence: 99%
“…2009]. Combination therapies seem to result in better compliance compared with monotherapies [Lin et al . 2012; Nichol et al .…”
Section: Cost-effectiveness Of the Fdc And Adherencementioning
confidence: 99%
“… 51 It has been found that combination therapies result in better compliance compared to monotherapies. 51 , 52 In addition, it has been shown that less frequent dosage enhances adherence, and technical adherence interventions are usually directed at simplifying the medication regimen. 53 Therefore, a potential advantage of the FDC of solifenacin/tamsulosin may be the improvement of patients’ adherence.…”
Section: Overview Of Studies On Tamsulosin Plus Solifenacin Combinatimentioning
confidence: 99%